Post vaginal hysterectomy serotonin syndrome - Downs, Christian M.; Hrynewych , Alexander (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Serotonin syndrome is a potentially fatal complication associated with the use of methylene blue dye and antidepressants. Methylene blue is a dye commonly used to visualize structures in OB/GYN surgeries. Due to difficulty in manufacturing other dyes, more physicians will likely have to use methylene blue, thus making the knowledge of its monoamine oxidase inhibition properties even more vital in the prevention of serotonin syndrome complications. Serotonin syndrome is a potentially deadly disease that has a high likelihood of occurring if methylene blue is used concurrently with any type of serotonin modulating agent. While it is listed as a black box warning when used with anti-depressants, it is still relatively rare but should be considered in cases such as these.